Form and function within a phylogenetic framework: Locomotory habits of extant predators and some Miocene Sparassodonta (Metatheria) - Ercoli, Marcos Darío (2012)
In this study, we analysed locomotory habits in extant predators and Sparassodonta species through geometric morphometric techniques and discriminant analyses of the distal humerus in anterior view, proximal ulna in lateral view, and tibia in proximal view. We included a wide sample of extant predators, and considered the phylogenetic and allometric structure in the data sets. We also included some Sparassodonta, a group of carnivorous metatherians that inhabited South America during the Cenozoic, and inferred their locomotory habits. Results suggest the presence of a close relationship between shape and locomotory habits, even after removing the shape component explained by phylogeny in the three postcranial elements. Terrestrial habits were inferred for Arctodictis sinclairi, Borhyaena tuberata, 'Lycopsis' longirostrus, and Thylacosmilus atrox. Some degree of cursoriality was highlighted in B. tuberata and T. atrox, and climbing abilities in 'L.' longirostrus, and to a lesser degree in B. tuberata. Scansorial habits were inferred for Cladosictis patagonica, Sipalocyon gracilis, Prothylacynus patagonicus, and Pseudonotictis pusillus, and in the case of C. patagonica, some digging ability was also tentatively inferred. © 2012 The Linnean Society of London.